2016
DOI: 10.1016/j.saa.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic characterizations of aluminum phenoxide

Abstract: A synthetic route to obtain crystalline aluminum phenoxide was established. Its molecular structure in solid-state and solution is unambiguously determined by single-crystal X-ray diffraction and (1)H, (13)C and (27)Al NMR spectroscopy. The single-crystal X-ray analysis revealed the presence of the dimeric THF adduct [Al(OPh)3·THF]2 with a disordered trigonal bipyramidal geometry at the aluminum atom which is bonded to a THF ligand, two terminal and two bridging phenoxy groups (OPh). The solution behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The oxygen atoms of the terminal and bridged aryloxide ligands and coordinated THF molecule form the distorted tetragonal bipyramidal coordination environment at the aluminum ion. The dimeric aggregation motif observed in [ 1· (thf)] 2 · (THF) 2 is similar to that found previously for aluminum phenoxide . The Al(1)–O(4) and Al(1)–O(4)* bonds within the central [Al­(μ-OAr) 2 Al] core are notably longer (1.832(2) and 1.917(2) Å) compared to the related Al(1)–O(1) and Al(1)–O(2) bonds involving the terminal aryloxides ligands (1.729(2) and 1.745(2) Å).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The oxygen atoms of the terminal and bridged aryloxide ligands and coordinated THF molecule form the distorted tetragonal bipyramidal coordination environment at the aluminum ion. The dimeric aggregation motif observed in [ 1· (thf)] 2 · (THF) 2 is similar to that found previously for aluminum phenoxide . The Al(1)–O(4) and Al(1)–O(4)* bonds within the central [Al­(μ-OAr) 2 Al] core are notably longer (1.832(2) and 1.917(2) Å) compared to the related Al(1)–O(1) and Al(1)–O(2) bonds involving the terminal aryloxides ligands (1.729(2) and 1.745(2) Å).…”
Section: Discussionsupporting
confidence: 81%
“…The 27 Al nuclear magnetic resonance (NMR) was employed to study the aggregation behavior for newly prepared compounds 1−7 in the THF-d 8 solution. Ultimately, we found that the resonance signal at δ( 27 Al) = 70 ppm, previously assigned to four-coordinated aluminum ions in aluminum aryloxide, 18 is apparently attributed to the background coming from the NMR probe of the spectrometer (Figure S1). A broad resonance signal around δ( 27 Al) = 30 ppm was detected in the series of homoleptic aryloxides 1−3.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Table S2: Coordinates of the geometry-optimized structures. Reference [51] is cited in the supplementary materials. Funding: This research received no external funding.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The Al-O distances span the range 1.763(1)-1.795(1) Å, which is marginally longer than those typically seen in terminal Al-O (phenoxy) bonds in neutral aluminium complexes such as Al2(OPh)6‧2THF [1.734(3) Å]32 or (tBu2(OPh)Al)2‧(µ-4,4'-bipy) [1.719(5) -1.755(4) Å].…”
mentioning
confidence: 93%